ANALISIS PERTIMBANGAN HAKIM PADA PERKARA PENGANIAYAAN YANG DISELESAIKAN MELALUI RESTORATIVE JUSTICE - Narnilawati Narnilawati; Ilka Sandela (jurnal.unprimdn.ac.id, 2023)
The crime of maltreatment is an act of assault against another person on the body, which causes pain and even the loss of one's life. Restorative justice is an approach to solving criminal cases through deliberations to obtain an agreement between the two parties. The persecution case Number 63/Pid.B/2021/PN.Skm was charged with Article 351 paragraph (1) of the Criminal Code, which was resolved through restorative justice even though, in the Decree of the Director General of the General Judiciary Agency Number 1691/DJU/SK/PS.00/12/ 2020 of severe crimes, restorative justice cannot be carried out, with the same post mortem results the judge concluded that the perpetrator's actions did not bring any danger to the victim. The purpose of this study was to find out the analysis of the judge's considerations in implementing Restorative Justice in case Number 63/Pid.B/2021/PN.Skm was charged with Article 351, paragraph (1) of the Criminal Code. The decision contradicted the decision of the director of general justice, and the judge gave an interpretation of different results of the same post-mortem submitted by the public prosecutor. The method used is a mixed method between normative and empirical methods that are widely used in this study is the normative method. The results of this study indicate that the settlement of severe crimes of persecution through restorative justice is contrary to the regulations of the General Judiciary Director General's Decree, and the results of the post-mortem examination submitted by the prosecutor and the panel of judges concluded that the defendant's actions did not pose any danger to the victim even though in fact the victim's condition at that time was severe